Current Expenditure Over the Term of Office: The Case of Polish Municipalities - Monika Banaszewska (Ekonomista)
This article sets out to examine fluctuations in municipal current expenditure over the course of the term of office. An empirical study was conducted on a sample of 2,479 Polish municipalities over the period 2008–2022. In addition to total current expenditure, the analysis also looked at its components, including current expenditure on salaries and allowances, grants for current tasks, benefits for natural persons, and current expenditure on the purchase of materials and services. To account for unobserved heterogeneity and the impact of the business cycle, panel models with fixed effects for municipalities and electoral terms were employed. The results indicate that the political budget cycle affects total current expenditure and is influenced by current expenditure on salaries and allowances, as well as grants for current tasks. In addition, the magnitude of the decrease in total current expenditure in the post-election year is found to be more pronounced in municipalities with a newly elected mayor, compared to municipalities where the incumbent mayor was re-elected.